Facilitating dual careers by improving resistance to chronic stress: effects of an intervention programme for elite student athletes - Sallen, J.; Hemming, K.; Richartz, A. (European Journal of Sport Science, 2018)
The starting point of this contribution is the potential risk to health and performance from the combination of elite sporting careers with the pursuit of education. In European sport science and politics, structural measures to promote dual careers in elite sports have been discussed increasingly of late. In addition to organisational measures, there are calls for educational-psychological intervention programmes supporting the successful management of dual careers at the individual level. This paper presents an appropriate intervention programme and its evaluation: stress-resistance training for elite athletes (SRT-EA). It comprises 10 units, each lasting 90 minutes. It is intended for athletes and aims to improve their resistance to chronic stress. The evaluation was carried out in a quasi-experimental design, with three points of measurement (baseline, immediately after, and three months after) and two non-randomised groups: an intervention group (n = 128) and an untreated control group (n = 117). Participants were between 13 and 20 years of age (53.5% male) and represented various Olympic sports. Outcome variables were assessed with questionnaires. Significant short- and mid-term intervention effects were explored. The intervention increased stress-related knowledge, general self-efficacy, and stress sensitivity. Chronic stress level, stress symptoms, and stress reactivity were reduced. In line with the intention of the intervention, the results showed short- and mid-term, small to medium-sized effects. Accordingly, separate measurements at the end of the intervention and three months later showed mostly positive subjective experiences. Thus, the results reinforce the hope that educational-psychological stress-management interventions can support dual careers.